One true loves : a novel - Reid, Taylor Jenkins (New Delhi: Washington Square Press, 2016)
A breathtaking love story about a woman unexpectedly forced to choose between the husband she has long thought dead and the fiancé who has finally brought her back to life.
Keywords: Man-woman relationships; Fiction